jenny solves x^2 + 2x- 3 = 0 and finds the solutions are x = -3 and 1 she then graphs the function and gets the graph shown how are the solutions related to the y-intercept?

Answer:
See explanation
Step-by-step explanation:
Jenny solves [tex]x^2 + 2x-3 = 0[/tex] and finds the solutions are [tex]x = -3[/tex] and [tex]x=1.[/tex]
So, she can write this equation as
[tex](x-(-3))(x-1)=0\\ \\(x+3)(x-1)=0[/tex]
The y-intercept is at [tex]x=0.[/tex] Substitute it into the previous equation:
[tex](0+3)(0-1)=3\cdot (-1)=-3[/tex]
From the graph, she can see that y-intercept is at point (0,-3), so y-intercept -3 is the product of solutions to the quadratic equation.
Answer:
On usatestperp its A: They are the same values.
Step-by-step explanation:
The x-intercepts are were the graph crosses the x-axis. From the graph you can see that it crosses at x = -3 and 1, which are the solutions. Therefore, they are the same values.